EFFECT OF SEED TREATMENT ON SEED QUALITY ENHANCEMENT IN CORIANDER - A. PRIYADARSINI, J. K. BEURA,; R. K. , TARAI; S . K SWAIN, A. K. KAR AND (The Bioscan, 2016)
An experiment was conducted with 40 seed samples of coriander collected from farmers field at Seed Technology Research, NSP (Crop), Orissa University of Agriculture and Technology, Bhubaneswar to study the quality status in comparision to TL seeds with respect to germination, field emergence and seed health. Germination of seed ranged from 36 to 51 % and almost all the seeds had germination % below the minimum prescribed standardof 65 %. The farmers seeds were found to be less vigorous having seedling length SVI-I (659.3 to 1048.6) and seedling dry weight (SVI-II) as 75.2 to 120.2 as compared to TL seed with 1064.4 and 151.4 respectively. Among seed treating chemicals, Carbendazim recorded maximum germination (72%) , field emergence (61%) and yield (90.5g green plant/m2 ), SVI-I (1366) and SVI-II (144) . Seed treatment with biocontrol agents revealed that Trichoderma vidide (8g/kg seed) gave highest germination %(71%), field emergence (65%)and yield ( 90.5 g/m2), SVI-I(1583),SVI-II (142) and found most effective in enhancing speed of germination (upto 5.32), minimum bacterial infection (18%). Based on the above study, it can be concluded that seed treatment with fungicide Carbendazim @ 3g/Kg is the most effective in enhancing quality of seeds saved by the farmers. But owing to so many problems in view of ecosystem and environment, seed treatment with Trichoderma viride @ 8g/Kg seed is found most effective in managing seed infection, seed quality and higher yield